Beyond the print—virtual paleontology in science publishing, outreach, and education. (July 2014) - Lautenschlager, Stephan; Rücklin, Martin
Abstract : Virtual paleontology unites a variety of computational techniques and methods for the visualization and analysis of fossils. Due to their great potential and increasing availability, these methods have become immensely popular in the last decade. However, communicating the wealth of digital information and results produced by the various techniques is still exacerbated by traditional methods of publication. Transferring and processing three-dimensional information, such as interactive models or animations, into scientific publications still poses a challenge. Here, we present different methods and applications to communicate digital data in academia, outreach and education. Three-dimensional PDFs, QR codes, anaglyph stereo imaging, and rapid prototyping—methods routinely used in the engineering, entertainment, or medical industries—are outlined and evaluated for their potential in science publishing and public engagement. Although limitations remain, these are simple, mostly cost-effective, and powerful tools to create novel and innovative resources for education, public engagement, or outreach.